2013
DOI: 10.1103/physrevb.88.024401
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of spin state of iron porphyrin by chemisorption on magnetic substrates

Abstract: One of the key factors behind the rapid evolution of molecular spintronics is the efficient realization of spin manipulation of organic molecules with a magnetic center. The spin state of such molecules may depend crucially on the interaction with the substrate on which they are adsorbed. In this paper we demonstrate, using ab initio density functional calculations, that the stabilization of a high spin state of an iron porphyrin (FeP) molecule can be achieved via chemisorption on magnetic substrates of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 28 publications
0
52
1
Order By: Relevance
“…The efficient spin manipulation has made these molecules an attractive choice for various kind of spin dependent electronics applications. [1][2][3][4] Metal phthalocyanines (M Pc) are porphyrinoid macrocyclic complexes and symmetric organic molecules with a metal atom (M ) at the center surrounded by four bonded N atom and four non bonded N atom. The phthalocyanine molecules do not have any out-of-plane ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient spin manipulation has made these molecules an attractive choice for various kind of spin dependent electronics applications. [1][2][3][4] Metal phthalocyanines (M Pc) are porphyrinoid macrocyclic complexes and symmetric organic molecules with a metal atom (M ) at the center surrounded by four bonded N atom and four non bonded N atom. The phthalocyanine molecules do not have any out-of-plane ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such differences, for all planar molecules investigated to date, the interaction between the magnetic moment of the molecules and that of metal substrates has been found to be FM (see Table 1). This has been attributed to the direct exchange path between the central metal ion and the substrate atoms as well as to an indirect superexchange path via the N atoms [29,43]. Only when O or graphene is intercalated between the molecules and the substrates the coupling has been found to be AFM (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is usually neglected for bulk systems with high symmetry. Recently, it has been shown that, for lowdimensional systems, e.g., clusters [24] and organometallic molecules with magnetic centers [18,25,26], this contribution, commonly denoted as T z , has a significant role. More interestingly, the spin-dipole contribution may have an opposite sign to that of spin moment, thereby reducing the effective moment (m eff = m s + 7 T z ), which is measured in XMCD experiments [27].…”
Section: Introductionmentioning
confidence: 99%